Dialectical Assurance Case using Structured Assurance Case Metamodel Notation - Nungki Selviandro; Ryan Adeputra Sutopo; Gia Septiana Wulandari (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
An assurance case is a document created to enable the exchange of information related to system safety and security among various system stakeholders, including suppliers, acquirers, operators, and regulators. It is essential to review such assurance cases to ensure their validity. The Structured Assurance Case Metamodel (SACM) is one of the languages that can be used to communicate assurance cases, and it offers various variants and expressive notations to facilitate this task. While creating assurance cases, it is necessary to consider dialectical notation with CounterArguments and CounterEvidence to explain situations where an assurance case has an incorrect value or can be countered. SACM classifies this notation as dialectical, and it is useful for reviewing and developing assurance cases. However, despite the usefulness of this approach, there is limited research on its effectiveness. Therefore, this study aims to explain dialectical notation in the SACM assurance case language and develop existing SACM applications. The application was developed to provide users who are already familiar with assurance cases, especially SACM, with a practical way of introducing dialectical notation. By doing this, we hope to expand the use of SACM and improve its effectiveness in communicating assurance cases among system stakeholders.